On imposture : Jean-Jacques Rousseau, literary lies, and political fiction - Margel, Serge (Studies in Continental thought., 2023)
"Imposture is an abuse of power. It is the act of lying for one's own benefit, of disguising the truth in order to mislead. For Jean-Jacques Rousseau, however, imposture is first and foremost power itself. In On Imposture, French philosopher Serge Margel explores imposture within Rousseau's Discourses, Confessions, and Emile. For Rousseau, taking power, using it, or abusing it are ultimately one and the same act. Once there's power, and someone grants themselves the means, the right, and the authority to force another's beliefs or actions, there is imposture. According to Rousseau, imposture can be found through human history, society, and culture. Using a deconstructionist method in the classic manner of Derrida, On Imposture explores Rousseau's thought concerning imposture and offers a unique analysis of its implications for politics, civil society, literature, and existentialist thought"--